Cost-Utility Analysis of Venous Thromboembolism Prophylaxis Strategies for People Undergoing Elective Total Hip and Total Knee Replacement Surgeries in the English National Health Service - Dawoud, Dalia M.; Wonderling, David; Glen, Jessica; Lewis, Sedina; Griffin, Xavier L.; Hunt, Beverley J.; Stansby, Gerard; Reed, Michael; Rossiter, Nigel; Chahal, Jagjot Kaur; Sharpin, Carlos; Barry, Peter (Frontiers in Pharmacology, 2018)
Background Major orthopaedic surgery, such as primarily elective total hip replacement (eTHR) and elective total knee replacement (eTKR), are associated with a higher risk of venous thromboembolism (VTE) than other surgical populations. Little is known, however, about the cost-effectiveness of VTE prophylaxis strategies in these populations. Aim The aim of this work was to assess the cost-effectiveness of these strategies from the English National Health Service perspective to inform NICE guideline (NG89) recommendations. Materials and Methods Cost-utility analysis, using decision modelling, was undertaken to compare 15 VTE prophylaxis strategies for eTHR and 12 for eTKR, in addition to “no prophylaxis” strategy. The analysis complied with the NICE Reference Case. Structure and assumptions were agreed with the guideline committee. Incremental net monetary benefit (INMB) was calculated, vs the model comparator (LMWH+ antiembolism stockings), at a threshold of £20,000/quality-adjusted life-year (QALY) gained. The model was run probabilistically. Deterministic sensitivity analyses (SAs) were undertaken to assess the robustness of the results. Results The most cost-effective strategies were LMWH for 10 days followed by aspirin for 28 days (INMB=£530 [95% CI: -£784 to £1,103], probability of being most cost-effective = 72%) for eTHR, and foot pump (INMB = £353 [95% CI: -£101 to £665]; probability of being most cost-effective =18%) for eTKR. There was considerable uncertainty regarding the cost-effectiveness ranking in the eTKR analysis. The results were robust to change in all SAs. Conclusions For eTHR, LMWH (standard dose) for 10 days followed by aspirin for 28 days is the most cost-effective VTE prophylaxis strategy. For eTKR, the results are highly uncertain but foot pump appeared to be the most cost-effective strategy, followed closely by aspirin (low dose). Future research should focus on assessing cost-effectiveness of VTE prophylaxis in the eTKR population.